2005
DOI: 10.1016/j.orthres.2005.03.016.1100230607
|View full text |Cite
|
Sign up to set email alerts
|

Differences in stability and bone remodeling between a customized uncemented hydroxyapatite coated and a standard cemented femoral stem A randomized study with use of radiostereometry and bone densitometry

Abstract: The custom made Unique® stem is designed to fit closely to the metaphyseal region of the femur in order to obtain maximum mechanical stability and optimal load transfer. Thirty‐seven patients (38 hips) with non‐inflammatory arthritis were randomized to the uncemented custom made Unique® stem or the Elite Plus stem inserted with cement. The patients have been followed clinically as well as with radiostereometry (RSA) and Dual‐energy X‐ray Absorptiometry (DXA) for 2 years. After 2 years the RSA result showed min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
(23 reference statements)
3
20
1
2
Order By: Relevance
“…However, these stems showed almost no further subsidence at the 1-year follow-up, thus indicating that they had stabilized-as did the femoral stem of the patient in this study with femoral fracture. These findings are consistent with other observations (Grant et al 2005). Subsidence seems to be tolerated in some uncemented hydroxyapatite-coated stem designs up until 1 year.…”
Section: Discussionsupporting
confidence: 93%
“…However, these stems showed almost no further subsidence at the 1-year follow-up, thus indicating that they had stabilized-as did the femoral stem of the patient in this study with femoral fracture. These findings are consistent with other observations (Grant et al 2005). Subsidence seems to be tolerated in some uncemented hydroxyapatite-coated stem designs up until 1 year.…”
Section: Discussionsupporting
confidence: 93%
“…It is accurate to ±47 µm, with a precision of 30 µm when monitoring femoral stem distal migration [12]. The RSA technique has been used to evaluate mid to long-term outcome, compare cementless and cemented stems, or, more commonly, assess the wear of the acetabular component of hip prostheses [13][14][15]. However, there are comparatively few studies evaluating early migration characteristics of cementless stems using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Arabmotlagh 40 suggested that preservation of BMD in zone 1 of some of their study group might have been due to the effects of HO, and a recent study examining femoral remodeling excluded a patient with ''extensive'' HO from analysis. 41 However, our study shows that merely excluding ''extensive'' HO is insufficient, as even mild HO produces a significant effect. The only BMD study comparing differences between patients with and without HO following THA is included in a study of biochemical markers of HO, 42 which showed no difference in BMD between the two groups.…”
Section: Discussionmentioning
confidence: 55%